Complete nucleotide sequence analysis of a Brazilian dengue virus type 2 strain - Flávia Barreto dos Santos; Marize Pereira Miagostovich; Rita Maria Ribeiro Nogueira; Dianna Edgil; Hermann Gonçalves Schatzmayr; Lee W Riley; Eva Harris (Memorias do Instituto Oswaldo Cruz, 2002)
In the last decade, dengue fever (DF) in Brazil has been recognized as an important public health problem, and an increasing number of dengue haemorrhagic fever (DHF) cases have been reported since the introduction of dengue virus type 2 (DEN-2) into the country in 1990. In order to analyze the complete genome sequence of a DEN-2 Brazilian strain (BR64022/98), we designed primers to amplify contiguous segments of approximately 500 base pairs across the entire sequence of the viral genome. Twenty fragments amplified by reverse transcriptase-PCR were cloned, and the complete nucleotide and the deduced amino acid sequences were determined. This constitutes the first complete genetic characterization of a DEN-2 strain from Brazil. All amino acid changes differentiating strains related to the Asian/American-Asian genotype were observed in BR64022/98, indicating the Asiatic origin of the strain.